The Cultural Debate in the Popular Unitiy: A Prior Question [el Debate Cultural en la Unidad Popular: Una Cuestión Previa (1958-1969)] - Laura de la Luz-Briceno, R (Universitat de Valencia, Faculty of Philology, Translation and Communication, 2021)
This article aims to examine where the conceptualizations and ideas expressed in the cultural debate of the Unidad Popular come from, specifying in the case of the proposal of the writer Enrique Lihn, who during this government acted as an intellectual committed to the socialist project. It is proposed that the practices of sociability of the writers in the 1960s, made possible the formation of a Latin American intellectual network, which produced and put into circulation, from a heterodox Marxism, the social function of literature, the commitment of the writer and the needs to create social and cultural conditions for the people to lead the process of social change. We share the idea that Salvador Allende s government represents the culmination of a series of intellectual processes in which the problem of culture in Latin America was thought of and Enrique Lihn s proposal, for the case of Chile, shows the action of writers as collective actors in the cultural and political field, willing to argue their proposals with the revolutionary government. © 2021 Universitat de Valencia, Faculty of Philology, Translation and Communication. All rights reserved.